Existence and Asymptotic Stability of Solutions for Hyperbolic Differential Inclusions with a Source Term. (18th March 2007) - Park, Jong Yeoul; Park, Sun Hye
Abstract : We study the existence of global weak solutions for a hyperbolic differential inclusion with a source term, and then investigate the asymptotic stability of the solutions by using Nakao lemma.